The Role of the Implementation of National Building Regulations in the Fire Safety Improvement of Industrial Structures - T Askaripoor; GA. Shirali; R. Yarahmadi; Elahe Kazemi (Iranian Journal of Health, Safety and Environment, 2016)
In accordance with national building regulations, human safety and health should not be compromised in any way by the structures. Noncompliance with existing standards can increase the risk of fire in buildings. This study aimed to assess the impact of national building regulations on the reduction of the fire risk level in an industrial structure. In this study, the fire risk level of the building and contents, occupants, and activities were calculated in a power plant control room using Fire Risk Assessment Method for Engineering (FRAME). In the following, by assessing the existing situation, the effect of the implementation of national building regulations was determined on the reduction of fire risk level. The result showed that the fire risk level for occupants (20.64), building and content (1.02) that are above the acceptable level and corrective measures and design changes should be applied to reduce the risk level. Also, in case of application of the third chapter of Iranian National Building Regulations in power plant construction, the fire risk level will be reduced by 11.7% compared to the existing situation This study showed that the implementation of national building standards and regulation can provide the occupants life safety by correctly predicting escape routes. Fire Risk Assessment Method for Engineering (FRAME) is a very effective tool for selecting the best control strategies for fire safety of industrial structures.